Bibliotecas Escolares: uma cartografia - CARDOSO, Juçara dos Santos (Universidade Federal do Oeste do Pará, 2021)
Based on the prevalent conceptions of library and school education, which indicate that the integration of these spaces within the institutions and their inclusion in the educational pro-cess collaborate for the teaching-learning of knowledges that transcend common sense and anchor in the critical and questionable sense of scientific culture, with significant role in the intellectual formation of students. Under this logic, this work aims to produce the cartography of the school libraries of the state education network of the municipality of Santarém, so as to verify how they are inserted in this discourse, analyzing the possibilities and difficulties of their contribution to the students ' intellectual training. The methodology used includes bio-graphical revision and conceptual study on reading, training, omnilateral formation and school library and visit in locus to collect data, iconographic documentation and conversation with the person in charge of the library (Those who act direct them or those who, in the absence of the directors, have authority over them). The results point out that from the universe of 30 schools, 25 have a space to function as a library. And five have good conditions of use, twelve reasonable, seven have precarious conditions and one has no conditions of use. Regard to the book collection, they all have reasonable collections and receive books from the FNDE (text-books, the teacher, literature and dictionaries). Except for four schools, all received collec-tions and furnishings of the project Alvorada in 2001. As for the operation, fourteen have busy professionals, in different shifts, and none of the schools attend the three shifts. Howev-er, it is possible to observe that the dynamics of functioning of the libraries we searched, in most cases, are restricted to loan and return of books activities. In the coming of the visits, it was possible to notice in some libraries the presence of students in search of literature books. The analysis points out that, while there is a relative awareness of the contribution of this space to the intellectual formation of pupils and in the schools space and reasonable collec-tions for the library to function, the absence of supervision, appreciation and professionals have resulted in the loss of value and functionality of these spaces, and consequently, a limita-tion in the learning of the student.